Masters of Success - Misner, Ivan; Morgan, Don (Ascent Audio, 2019)
Who has not admired the titans of sport, entertainment, commerce, and public service and been inspired to set course by those stars? What youth has not dreamed of becoming rich and famous? What restless fast-food manager has not dreamed of being the boss of a nationwide restaurant chain? What hard-working employee has not dreamed of running his own company? Perhaps more important, what can they, and we, learn about achieving success from successful people? This is the magic of Masters of Success.